2017
DOI: 10.3928/01477447-20170925-06
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Cortical Button Stabilization of Isolated Acute Neer Type II Fractures of the Distal Clavicle

Abstract: Neer type II distal clavicle fractures are inherently unstable. The purpose of this study was to review the outcome of Neer type II distal clavicle fractures arthroscopically treated using a suspensory cortical button technique. Between 2008 and 2012, a total of 17 Neer type IIB fractures were managed operatively at the authors' institution. Functional outcomes were assessed using the pain score, the Disabilities of the Arm, Shoulder and Hand score, the Penn Shoulder Score, and the American Shoulder and Elbow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The 15 included articles consisted of 8 retrospective cases series reporting on a single fixation technique, 7,13 17,27,32 5 prospective case series that reported on a single fixation technique, 4,12,19,24,31 and 2 retrospective comparative studies. 9,34 All but 1 study 14 provided data on union rates and functional outcome scores, and this study was excluded when deriving a mean.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 15 included articles consisted of 8 retrospective cases series reporting on a single fixation technique, 7,13 17,27,32 5 prospective case series that reported on a single fixation technique, 4,12,19,24,31 and 2 retrospective comparative studies. 9,34 All but 1 study 14 provided data on union rates and functional outcome scores, and this study was excluded when deriving a mean.…”
Section: Resultsmentioning
confidence: 99%
“…4,13,19 Most authors reported that union was achieved at the end of the follow-up period, while some described the date of earliest radiographic union. 4,9,12,13,24,31 Bony union was reported in 208 of the 221 (94.1%) fractures. Of the 13 reported nonunions, only 4 (30.8%) were symptomatic and required revision surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did report 2 cases of asymptomatic nonunion and 1 fixation failure requiring revision with plate osteosynthesis. Most recently, Blake et al 5 performed arthroscopic cortical button fixation on 17 patients with Neer type II distal clavicle fractures using a TightRope device. Despite excellent functional outcomes, the authors did report a 17.5% nonunion rate and a hardware-related complication requiring implant removal.…”
Section: Discussionmentioning
confidence: 99%
“…Its biomechanical excellence has been proven by recent articles, and several actual clinical cases with favorable outcomes have also been reported 2345). Moreover, the indication for this technique is expanding because the technique can be used for not only the AC joint dislocation, but also acute distal clavicle fractures with CC ligament disruption 6). However, it is technically demanding, and the process of creating an anatomically accurate bone tunnel through the distal clavicle and small coracoid process can be difficult.…”
mentioning
confidence: 99%